KAJIAN KAPASITAS DAN EFEKTIVITAS RESIN PENUKAR ANION UNTUK MENGIKAT KLOR DAN APLIKASINYA PADA AIR - I K. G. Antara; I W. Budiarsa Suyasa; A. A. Bawa Putra (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2008)
This paper reports a research on the capacity and efficiency of resin anion exchange on chloride in a batchsystem. The system was then applied to chloride level in spring water in Sedang Village. Chloride content analysedwere using argentometry methode .The results of the research showed that resin was potential to reduce chloride level below Water QualityLimit for (Group B). Its capacity was 0.6462 mg/g and saturating time was 260 minutes. Its effectiveness between64.50% - 97.04%.The analysis of spring water in Sedang Village showed that these springs were contaminated with 260.33 –295.83 ppm chloride. The resin exchange applied to these waters reduced the chloride levels to the level below theGuideline Limit for the 250 mg/L purposes (Group B).